Mechanical Thrombectomy in Isolated Occlusion of the Proximal Posterior Cerebral Artery - Herweh, Christian; Abdalkader, Mohamad; Nguyen, Thanh N.; Puetz, Volker; Schöne, Daniela; Kaiser, Daniel; Chen, Chih-Hao; Jeng, Jiann-Shing; Möhlenbruch, Markus A.; Ringleb, Peter A.; Nagel, Simon (Frontiers in Neurology, 2021)
Endovascular therapy (EVT) is established as first line treatment for acute ischemic stroke (AIS) due to large vessel occlusion (LVO) in the anterior circulation. For basilar artery occlusion, recent randomized clinical trials demonstrated equipoise but also advantages for EVT under particular circumstances. It remains unclear whether EVT offers an advantage over best medical management (BMM) including thrombolysis (IVT) in isolated occlusion of the proximal posterior cerebral artery (PCAO). 1.2 Methods Patients with AIS due to PCAO proven by CT or MR angiography were retrospectively identified from local databases at four comprehensive stroke centers in Germany, USA and Taiwan between 2012 and 2020. Demographic and clinical data were collected and imaging characteristics including pretherapeutic, interventional and follow up imaging were reviewed locally at each center. Patients were grouped according to therapy, i.e., BMM including IVT alone versus BMM and EVT. Efficacy endpoints were early neurological improvement (ENI) after 24 hours or at discharge, good outcome (modified Rankin scale 0-2) after 3 months, as well as hemorrhagic complications and in-house deaths as safety endpoints. 1.3 Results We included 130 patients of whom 23 (17.7%) received EVT. EVT patients had more proximal occlusions (69.9% vs. 43%, p=0.023) and had a better premorbid function (premorbid mRS 0 (0-4) vs. 1 (0-3), p<0.01) when compared to BMM patients. IVT showed a trend towards being less performed in the EVT group (21.7% vs. 41.1%, p=0.1), while other baseline parameters were balanced. Successful reperfusion was achieved in 52% of EVT patients. ENI was more frequent in the EVT group (61% vs. 35.5%, p=0.034). Good outcome at 90 days and safety endpoints did not differ. In a bivariate analysis, ENI was independently predicted by the use of EVT (OR 2.76; CI: 1.055-7.04) and the baseline NIHSS (OR 1.082; CI: 1.027-1.141 per point increase). 1.4 Discussion EVT in isolated PCAO appears safe and feasible. Positive effects on clinical outcome are primarily on ENI but also depend on the initial stroke severity. Further prospective or randomized studies are needed to better describe the potential long term clinical benefits of EVT for PCAO as compared with best medical management.